Diversi Dalam Kasus Persetubuhan Yang Dilakukan Oleh Anak - Resimanuk, Tesalonika Altje; Wadjo, Hadibah Zachra; Tuhumury, Carolina (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Diversion can be carried out based on Article 7 (seven) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and based on Article 3 of Supreme Court Regulation Number 4 of 2014 concerning Guidelines for the Implementation of Diversion. But in fact, when the case of intercourse by this child reached the court stage, the judge thought that diversion could be carried out and resulted in a diversion agreement, namely being placed in the Social Welfare Organizing Institution (LPKS) for 3 (three) monthsPurposes of the Research: The aim of the research is to examine and discuss how diversion is in cases of sexual intercourse by children. To examine and discuss the impact of diversion in cases of sexual intercourse by childrenMethods of the Research: The research method used is normative juridical. The problem approach used is the Conceptual Approach, Legislation Approach, and Case Approach. The legal materials used are primary legal materials and secondary legal materials. Collection of legal materials using literature study and analyzed using qualitative analysis methods.Results of the Research: Based on the results of the research and discussion that has been carried out, it can be seen that the settlement of cases taken by the authors has not been fully implemented properly, where the application of diversion against children has not been on target because it can be seen from the crime committed by the child, namely intercourse. Children really need to get good legal protection by the state. But what needs to be known is that diversion is not a peaceful effort against children in conflict with the law with victims or their families, but a form of punishment against children who are in conflict with the law in an informal way. Judging from the crime committed, diversion cannot be carried out because this cannot have a deterrent effect on children and the possibility of doing so in the future may occur. From the problems that occur, the impact will be positive or negative. The positive impact is that children can avoid the stigmatization of bad children from society and can make it easier for children to interact with society again. On the other hand, the negative impact is that it does not have a deterrent effect on the child